Analisis Makna Penamaan Makanan Madura : Kajian Semantik - Evi Pebri Ila Rachma (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
This study aims to describe the meaning of the Madurese food name. This research is qualitative and descriptive. The data sources for this study are documents. The instrument in this study is researchers who play an active role in data acquisition in the field. The data source is a document, and the data for this research is Madurese food names. The results of this study show the types of meanings in Madurese foods are lexical, referential, denotative, connotative, and associative.